Kinetic Study of the Dissolution of Tunisian Natural Phosphate or Francolite in Industrial Phosphoric Acid - CHAABOUNI, Ahmed (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
A kinetic study of dissolution of Tunisian natural phosphate or francolite whose particles have a mesoporous texture in industrial phosphoric acid is carried out. Therefore, We focused on the study of the influence of certain parameters that are close to those used in plants producing phosphoric acid which are the stirring speed (300, 500 and 700 rounds per minute), concentration of phosphoric anhydride (25, 30 and 35 percent of P2O5), and the temperature (60, 70 and 80 degrees Celsius); we note that the rate of dissolution of this phosphate rises by increasing the precedent parameters. Because of the complexity of the study of the dissolution of phosphate in mineral acids. Several different published kinetic models giving different expressions of speed versus time. The shrinking core model is the appropriate model used in our work in a solution where there is no calcium sulfate to calculate the rate constant k and the activation energy Ea = 3.3946 Kcal/mol of this phosphate.